2021
DOI: 10.1021/acsomega.1c03889
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Simulation Study on the Density Behavior of n-Alkane/CO2 Systems

Abstract: The density and volumetric behavior of three typical n-alkanes (hexane, octane, and decane) influenced by different mole fractions of CO2 injected in them at temperatures from 303 to 363 K and pressures from 3.8 to 8.67 MPa were investigated by performing molecular dynamics simulations. It is shown that the mass density first increases and then decreases with increasing CO2 mole fraction. Correspondingly, the system volume only slightly swells at low CO2 contents while suddenly expanding when the CO2 mole frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Therefore, CO 2 plays a dual role in this process, causing oil to expand and separating it from the surface of quartz. 42 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, CO 2 plays a dual role in this process, causing oil to expand and separating it from the surface of quartz. 42 …”
Section: Resultsmentioning
confidence: 99%
“…As a result, the CO 2 –octane system expands further, providing more space for the diffusion of CO 2 . The swelling process of the CO 2 –octane binary system is shown in Figure 6 [ 80 ]. It was also found that when CO 2 was injected into the system, the alkane chain was slightly extended, meaning that the presence of CO 2 molecules caused the alkane molecules to expand, which further led to the expansion of the systemic volume.…”
Section: Main Mechanism Of Sc-co 2 Flooding Of Hea...mentioning
confidence: 99%
“… Simulation snapshot of swelling of CO 2 –octane system at P = 7.69 MPa and T = 333 K: ( a ) t = 0, ( b ) 20, ( c ) 100, ( d ) 300, ( e ) 1000, and ( f ) 1500 ps. Color code:C 8 H 18 (black) and CO 2 (red) [ 80 ]. …”
Section: Figurementioning
confidence: 99%